Design and development of a photovoltaic power system for automatic bean sprout - Muhammad Nurzuhaili, Zainudi (2012)
Nowadays, the use of renewable energy has been increasingly widespread. One of the renewable energy that is now gaining attention is the use of solar power. In Malaysia, the use of solar power is particularly suitable for our country due to the equatorial climate in which our country is experiencing summer and humid throughout the year. There are a lot of applications in solar power that can be implemented. One of which is in the agricultural industry. Most crops require intensive care to produce quality results, while giving considerable returns to operators. Among the factors that influence the quality of the production of crops such as bean sprout, are sources of water. Bean sprout need plenty of water resources to produce good growth. An irrigation system to watering the seeds regularly is needed and at the same time to make sure the seeds are enough of water resources. This project concerns in designing an automatic system for bean sprout which integrate with the solar power system. The development of hardware consists of charging circuit, relay circuit which will integrate with microcontroller for controlling the water pump. The software is the development of PIC 18F4550 micro-controller software program that performs delays which will control the operation of water pump.